Att sörja en levande: Om sorg och manlighet i skilsmässorelaterade livskriser - Ljung-Hagborg, Anna (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2006)
The purpose of this article is to illustrate how different voluntary and professional crises groups for men deal with the grief in relation to divorce related life crises. The different kinds of organisations deal with the emotional aspects of the divorce in different ways, but they share the assumption that grief is a kind of work (either in the sense that the person has to work their way through the grief step by step, or actively engage in changing the way he feels or acts in relation to the circumstances of the divorce). I argue that although grieving people always are a source of cultural distress, this distress is further accelerated in the environments I have explored. The reason of this acceleration is the fact that cultural beliefs of the "dangerous" or problematic emotional lives of men, have deep historical roots, and are constantly emphasized in contemporary representations of masculinities. In my study I focus on three different aspects of this unpredictability: how the social environment deals with the practical and emotional dimensions of the divorce. How the men try to cope with a situation where the future is unsure, or where the picture that they have of themselves falls apart. The strategies used by crises centres can in this meaning be seen as different instruments to create order and deal with uncertainty.